2006
DOI: 10.1051/vetres:2006027
|View full text |Cite
|
Sign up to set email alerts
|

Cellular gene expression survey of PseudoRabies Virus (PRV) infected Human Embryonic Kidney cells (HEK-293)

Abstract: -Pseudorabies virus (PRV)is an alpha herpesvirus that causes Aujezsky disease in the pig. To characterize the impact of PRV infection on cellular expression, we used microarrays consisting of 9850 oligonucleotides corresponding to human genes and examined the expression levels of mRNA isolated 0.5, 3, 6, and 9 h post infection (hpi) from cultures of infected HEK-293 cells. Very few changes were observed during the first 3 h of infection but significant modifications in the cell expression of more than 1000 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…An important question that remains is whether the proteases involved are of cellular and/or viral origin. Interestingly, transcriptome studies have indicated that several cellular components involved in trypsin-like serine protease activity are differentially regulated upon infection with alphaherpesviruses like PRV and HSV, including factor IX, tissue-type plasminogen activator (t-PA) and urinary plasminogen activator receptor 1 (uPAR1) [30,31]. Further research will be aimed at identifying the proteases involved and elucidating the exact molecular mechanism of viral penetration through the BM.…”
Section: Discussionmentioning
confidence: 99%
“…An important question that remains is whether the proteases involved are of cellular and/or viral origin. Interestingly, transcriptome studies have indicated that several cellular components involved in trypsin-like serine protease activity are differentially regulated upon infection with alphaherpesviruses like PRV and HSV, including factor IX, tissue-type plasminogen activator (t-PA) and urinary plasminogen activator receptor 1 (uPAR1) [30,31]. Further research will be aimed at identifying the proteases involved and elucidating the exact molecular mechanism of viral penetration through the BM.…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, DNA microarray technology has proven to be a very efficient high-throughput tool to study the gene expression profiles of infected host cells or pathogens [ 10 , 11 ]. To date, three transcriptomic analyses focused on cellular gene expression have been carried out in non-porcine PrV infected cells [ 12 - 14 ]. Ray and Enquist have compared the cellular pathways regulated by PrV and HSV-1 during infection of rat embryonic fibroblast cells using a rat microarray [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HSV-1 ICP27, the PrV homolog pUL54 is dispensable for virus replication in cell culture (47,49). Transcript analyses of PrV-infected rat (44), human (6), and porcine (12) cells demonstrated alterations in the abundance of individual cellular transcripts, which resulted in the depletion or accumulation of specific mRNAs. Of the 9,850 genes examined in one study (6), the number of significantly up-or downregulated genes increased from approximately 1,000 to over 2,400 between 6 and 9 h after infection.…”
mentioning
confidence: 99%
“…Transcript analyses of PrV-infected rat (44), human (6), and porcine (12) cells demonstrated alterations in the abundance of individual cellular transcripts, which resulted in the depletion or accumulation of specific mRNAs. Of the 9,850 genes examined in one study (6), the number of significantly up-or downregulated genes increased from approximately 1,000 to over 2,400 between 6 and 9 h after infection. Evaluation of the functions annotated for highly regulated cellular genes shows that PrV infection influences numerous cellular pathways and that genes involved in protein and nucleic acid metabolism, signaling, transport, cell cycle control, adhesion, transcription, the stress response, and innate immunity are affected most frequently.…”
mentioning
confidence: 99%